Price Volatility of Milkfish Commodities in Aouth Sulawesi - Muhammad Irwandhi Amri; Ratnawati Tahir; Syafiuddin; Sri Mardiyati; Mohammad Natsir; Irma Sribianti (IECON: International Economics and Business Conference, 2024)
Milkfish is an important fisheries commodity in South Sulawesi, both for domestic consumption and as an export product. However, the high price volatility of milkfish often poses challenges for producers, traders, and consumers. This study aims to analyze the price volatility of milkfish in South Sulawesi from 2018 to 2023, using secondary data on producer prices and total milkfish production. The analysis methods include calculating the coefficient of variation and linear trend analysis to measure price fluctuations and trends over the period. The results indicate significant price fluctuations, especially in 2020 and 2021, which were influenced by supply chain disruptions due to the COVID-19 pandemic. Overall, milkfish prices have shown a steady increase from 2018 to 2023, despite sharp price spikes in certain periods. Factors affecting price volatility include production levels, distribution policies, and external factors such as extreme weather and the pandemic. This study provides insights into the price patterns of milkfish and the factors influencing price fluctuations, which can serve as a basis for formulating more effective policies to stabilize the milkfish market in South Sulawesi.